The Influence of Organizational Climate and Work Motivation on the Performance of Basic Education Teachers - Erniati; Musdiani; Sari, Siti Mayang (Indonesian Journal of Instructional Media and Model, 2024)
This research aims to determine the influence of organizational climate and work motivation on the performance of basic education teachers in Gugus 04 Indrajaya, Pidie Regency. The time of the research was in March 2024. The research population was 85 people and 41 people were sampled purposively. This research is quantitative research, using survey methods. Data collection techniques through observation, documentation and questionnaires. The data analysis technique uses multiple linear regression analysis. The results of data analysis show that the Organizational Climate variable (X1) partially has a significant effect on Performance (Y). The work motivation variable (X2) partially has a significant effect on performance (Y). The variables organizational climate (X1) and work motivation (X2) simultaneously have a significant effect on the performance (Y) of basic education teachers in Gugus 04 Indrajaya, Pidie Regency with a calculated F value of 54,599 and a sig value of 0.000. The coefficient of determination (R2) obtained a value of 0.742, indicating that the contribution of organizational climate and work motivation variables to teacher performance was 74.2%, while the remaining 25.8% was the contribution of other factors.